Community Level Factors Influencing Contraceptives Use among Pastoralist Women in West Pokot County, Kenya: A Community- Based Cross-Sectional Study - Lopar, Samuel K.; Kipmerewo, Mary C.; Chebor, Alex K. (Evidence-Based Nursing Research, 2025)
Context: Family planning is an essential aspect of reproductive health, crucial for controlling population growth, improving maternal and child health, and empowering women. However, its use in the pastoralist communities is still low. There is limited evidence about the determinants for non-utilization of contraceptives by marginalized populations. Aim: The study assesses community-level determinants affecting contraceptive usage among pastoralist women in West Pokot County, Kenya. Methods: The study employed a community-based, cross-sectional, correlational design involving 578 women aged 15–49 years. Multistage sampling was used, with 40 out of 115 community units being sampled. Quantitative data were gathered through a structured interview questionnaire, while the key informant guide and focused group discussion guide were used for qualitative data. Results: The study shows that 328(56.7%) of the respondents were aged between 14 and 29 years. The majority, 514(88.9%) of the respondents were married, and only 33(5.7%) were singles. The findings reveal religion support (p<0.001), cultural support (p<0.039), discussion with spouse (p<0.001), person who decided number of children (p<0.043), type of health facility seeking services from, and instances that could not access Family Planning method were associated with the uptake (p<0.05). Religion support (OR= 1.80; 95% CI: 1.31-2-46), cultural support (OR= 1.54; 95% CI: 1.02-2.32), discussion on family planning method with husband (OR= 2.46; 95% CI: 1.8- 3.37), who decides number of children jointly (OR=1.48; 95% CI: 1.00-2.17, p=0.043), and type of health facility seeking family planning services, private clinic (OR= 1.99; 95% CI: 0.99-3.97, p=0.051) and faith based facility (OR= 2.91; 95% CI: 1.26- 6.72, p=0.012) were markedly correlated with the use of family planning. Qualitative data identified distance and cost as significant barriers to accessing family planning. A participant had this to say: “You can get family planning methods in a government hospital, but it is not always easy to get there because it is far (distance) from where we live...". Conclusion: The study concludes that socio-cultural factors and social norms influence the use of contraception within the pastoral community; their culture favors large families, gives men and mothers-in-law a say in making reproductive health choices. Health system factors were also identified as influencing family planning uptake; facility type and distance to a health facility were major factors.
Keywords: Contraceptive use; community; pastoralist; West Pokot; women